Innovation in Group Guidance Media: E-Guide to Theraplay Based on Traditional Games for Children with Autism - Anis Tri Yuliana; Adirasa Hadi Prasetyo; Tantri Safitri; Faizatul Muflihah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This research aims to develop innovative products in the form of group guidance media and e-guides on traditional game-based techniques for children with autism. This research uses the Research and Development (R&D) method, adopting the Borg & Gall development model, which is modified as needed. The development stage includes preliminary studies, planning, initial product manufacturing, expert testing, and product revision. Validation was conducted by two learning media experts, two counseling guidance experts, and two guidance and counseling teachers at SLB, who served as potential users. Quantitative data were collected using assessment instruments on a 1-4 scale and analyzed using the Aiken inter-rater agreement technique, while qualitative data in the form of expert input were analyzed descriptively and interpretively through triangulation. The results showed that the product received an overall validity index of 0.96 from media experts, 0.89 from BK experts, and 0.95 from potential users, all classified as "high". The content's accuracy and clarity are considered adequate, with some improvement suggestions that have been integrated into the product revision. These products are not only considered appropriate in terms of design and usability but are also culturally relevant because they integrate traditional games as an intervention medium. The conclusion of the study indicates that the traditional game-based Theraplay technique e-guide is feasible, practical, and effective for use as a group guidance medium in services for children with autism in Indonesia, while supporting the preservation of local wisdom through an adaptive counseling approach. Keywords: group guidance media, the theraplay technique, traditional games, autism